2014
DOI: 10.1080/1540496x.2014.1013862
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Turkey’s Trilemma Tradeoffs

Abstract: We study the trilemma configuration of the Turkish economy for the pe-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…They also found that the implemented trilemma policies do not deviate substantially from optimal level. Akcelik et al (2014) studied the trilemma hypothesis for the Turkish economy covering the period 2002-2011 by employing Kalman filter to capture the time-varying character of trilemma policy combinations. They first test the validity of trilemma constraint assuming linearity among trilemma indices, and then investigated the role of foreign reserves on the trilemma trade-off.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also found that the implemented trilemma policies do not deviate substantially from optimal level. Akcelik et al (2014) studied the trilemma hypothesis for the Turkish economy covering the period 2002-2011 by employing Kalman filter to capture the time-varying character of trilemma policy combinations. They first test the validity of trilemma constraint assuming linearity among trilemma indices, and then investigated the role of foreign reserves on the trilemma trade-off.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Taguchi (2011) finds that the foreign exchange reserves serve as an anchor for macroeconomic policy and increase market confidence in a country's economic strength. A greater level of foreign reserve alleviates the 'fear of floating' due to smaller impacts from external monetary shocks that transmit via the exchange rate pass-through effect (Akcelik et al, 2014). A higher foreign reserve is therefore reducing the dependence of domestic interest rate to foreign interest rate while the upward pressure from higher foreign reserve to the domestic monetary base decreases with the increasing bank reserves requirement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A higher foreign reserve is therefore reducing the dependence of domestic interest rate to foreign interest rate while the upward pressure from higher foreign reserve to the domestic monetary base decreases with the increasing bank reserves requirement. These factors contribute to a positive impact of foreign reserves in achieving a balance between the trilemma issue (stable exchange rate, high financial integration and high monetary independence) in emerging countries which in turn promote the domestic monetary independence (Akcelik et al, 2014). Nevertheless, some studies also proposed an opposite view.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Country‐specific empirical studies conducted on the trilemma trade‐off include Akcelik et al . (), who examine the macroeconomic trilemma for Turkey using a Kalman filter and find strong evidence of the trilemma trade‐off holding. They also find that the role of foreign reserves has a significant dampening effect on the trilemma trade‐off in Turkey (Akcelik et al ., ).…”
Section: Literature Reviewmentioning
confidence: 99%